Springback analysis of thin tubes under torsional loading / Vikas Kumar Choubey, Mayank Gangwar and J. P. Dwivedi - Choubey, Vikas Kumar; Gangwar, Mayank; Dwivedi, J. P. (UiTM Press, 2010)
Springback, the elastic recovery of material on the release of applied load, is the major factor in obtaining the accurate and consistent dimensions of the final parti The mechanics of springback is essential for its effective prediction and compensation. The aim of the paper is to present a theoretical analysis of the torsional springback in thin tubes ofbi-linear work hardening material. The bi-linear behavior of the material is approximated by using modified Ludwik type stress-strain relation. The theoretical analysis is based on membrane and sand heap analogies. The analytical calculations establishes relationship for angle of twist to twisting moment and residual/springback angle of twist per unit length for thin tubes under plastic torsion in non-dimensionalized form. The theoretical analysis is supported by experiments performed on thin tubes of mild steel and aluminium with different geometry and mechanical properties. A comparison between the results obtained for thin tubes on bi-linear and nonlinear work-hardening material loaded under torsion is also made.